Maternal Consumption of Milk or Dairy Products During Pregnancy and Birth Outcomes: A Systematic Review and Dose-Response Meta-Analysis - Huang, Donghui; Wu, Qijun; Xu, Xin; Ji, Chao; Xia, Yang; Zhao, Zhiying; Dai, Huixu; Li, Hang; Gao, Shanyan; Chang, Qing; Zhao, Yuhong (Frontiers in Nutrition, 2022)
Purpose: This study aimed to systematically review current evidence and quantitatively evaluate the associations between milk or dairy consumption during pregnancy and birth outcomes. Methods: This systematic review had been reported in accordance with the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A supplementary literature search in PubMed, Web of Science, Cochrane Library, and Embase was conducted on 30 March 2021. Studies that assessed the association of maternal consumption of milk or dairy with birth-related outcomes were identified. The dose-response meta-analyses of continuous data and categorical data were applied. One-stage approach and two-stage approach were used where appropriate. Results: In total, 42 studies were eligible for the present systematic review, and 18 of them were included in the outcome-specific meta-analyses. The dose-response meta-analysis (Number of studies [N]=9) predicted a maximum mean change in birthweight of 63.38 g (95% Confidence Interval [CI]=0.08, 126.67) at 5.00 servings per day. Intake of dairy products had the greatest protective effect on small for gestational age at a maximum of 7.2 servings per day (Relative risk [RR]=0.69, 95% CI=0.56, 0.85) (N=7). The risk of large for gestational age was predicted to be maximum at 7.20 servings per day of dairy consumption, with the RR and 95% CI of 1.30 (1.15, 1.46) (N=4). In addition, the relationship between dairy consumption and low birth weight (RR=0.70, 95%CI=0.33, 1.50) (N=5) and premature birth (RR=1.13, 95% CI=0.87, 1.47) (N=5) was not significant, respectively. Conclusions: Maternal consumption of dairy during pregnancy has a potential effect on fetal growth. Further well-designed studies are warranted to clarify the specific roles of individual dairy products.